A German version of the oral impacts of daily performances: reliability and validity - Klotz, Anna-Luisa; Prager, Denis; Rammelsberg, Peter; Hassel, Alexander J.; Zenthöfer, Andreas (Clinical oral investigations, 2024)
The Oral Impact of Daily Performances (OIDP) is a dental patient-reported outcome measure (dPROM) for the estimation of oral health-related quality of life (OHRQoL) and takes the frequency as well as the severity of problems into account; however, it is not available in German language. The aim of this study was, therefore, to evaluate the reliability and validity of the German version of the OIDP in patients of a private practice.